Mild malformations of cortical development in sleep‐related hypermotor epilepsy due to KCNT1 mutations. Issue 2 (25th December 2018) - Rubboli, Guido; Plazzi, Giuseppe; Picard, Fabienne; Nobili, Lino; Hirsch, Edouard; Chelly, Jamel; Prayson, Richard A.; Boutonnat, Jean; Bramerio, Manuela; Kahane, Philippe; Dibbens, Leanne M.; Gardella, Elena; et al.
Abstract: Mutations in the sodium‐activated potassium channel gene KCNT1 have been associated with nonlesional sleep‐related hypermotor epilepsy (SHE). We report the co‐occurrence of mild malformation of cortical development (mMCD) and KCNT1 mutations in four patients with SHE. Focal cortical dysplasia type I was neuropathologically diagnosed after epilepsy surgery in three unrelated MRI‐negative patients, periventricular nodular heterotopia was detected in one patient by MRI. Our findings suggest that KCNT1 epileptogenicity may result not only from dysregulated excitability by controlling Na+K+ transport, but also from mMCD. Therefore, pathogenic variants in KCNT1 may encompass both lesional and nonlesional epilepsies.